Financial Management Based on SSP (Smart School Program) Mobile Application to Accelerate Education Services at Pondok Darul Arqam Muhammadiyah Patean in 2022 - Sucipto Sucipto; Fitri Nur Mahmudah (Ridwan Institute, 2023)
The purpose of this study is to determine the effect of financial management based on the mobile PSP (Smart School Program) application on the acceleration of educational services at Pondok Darul Arqam Muhammadiyah Patean Kendal in 2022. This research uses qualitative research methods with a library research approach. This method is used to collect data and information from various relevant sources, such as scientific journals, books, research reports, and other documents. The library research approach allows researchers to collect and analyze data thoroughly by referring to existing literature reviews. In conclusion, this study provides evidence that the use of PSP Mobile application-based financial management has a positive impact on the acceleration of education services. The practical implication of this research is that decision makers and practitioners in the field of education can consider implementing PSP Mobile applications as a strategy to improve the efficiency and effectiveness of Education services.